Therapeutic potential and mechanisms of repetitive transcranial magnetic stimulation in Alzheimer’s disease: a literature review - Xinlei Zhang; Lingling Zhu; Yuan Li; Hongna Yu; Tao Wang; Xiuli Chu (European Journal of Medical Research)
Abstract Alzheimer’s disease (AD) is the most prevalent neurodegenerative disorder, affecting tens of millions worldwide with projections indicating increasing prevalence in coming decades. Characterized by progressive cognitive decline, AD manifests with varying degrees of executive, language, and visuospatial impairments that worsen over time, eventually leading to severe psychiatric symptoms, mobility difficulties, sleep disturbances, and incontinence. While pharmacological treatments remain the primary intervention approach, their efficacy often diminishes over time and may produce significant adverse effects. Repetitive transcranial magnetic stimulation (rTMS), as a non-invasive neuromodulation technique, has emerged as a promising alternative or complementary therapy. This literature review examines the therapeutic potential and mechanisms of rTMS in Alzheimer’s disease. Through electromagnetic induction, rTMS can selectively modulate cortical excitability, with high-frequency stimulation (≥ 5 Hz) enhancing neural excitability and low-frequency stimulation (≤ 1 Hz) producing inhibitory effects. Recent clinical evidence demonstrates that rTMS can significantly improve cognitive function, memory, language abilities, and motor performance in AD patients, particularly when administered with optimized parameters targeting key brain regions, such as the dorsolateral prefrontal cortex. The neurobiological mechanisms underlying these effects include enhanced synaptic plasticity, increased expression of neurotrophic factors, modulation of neurotransmitter systems, and reduction of pathological protein aggregation. Meta-analyses indicate that high-frequency protocols (particularly 20 Hz) delivered over at least 3 weeks with a minimum of 20 sessions produce the most significant cognitive improvements, with effects potentially persisting for months post-treatment. Combined approaches integrating rTMS with cognitive training show particular promise through synergistic enhancement of neuroplasticity. Despite encouraging results, standardization of treatment protocols and larger clinical trials are needed to establish definitive guidelines and determine long-term efficacy. This review synthesizes current evidence supporting rTMS as an effective intervention for alleviating clinical symptoms of Alzheimer’s disease while highlighting opportunities for advancing its therapeutic application.